Merancang Alat Pendeteksi Boraks Pada Bakso Menggunakan Metode Logika Fuzzy Berdasarkan Sensor Warna Dan LED (Light Emitting Diode) Berbasis Android - Turilah, N H; Sudarsana, I W; Lusiyanti, D (Program Studi Matematika, Universitas Tadulako, 2020)
ABSTRACT Meatballs are foods made from meat, shrimp, fish chopped and crushed together with starch and egg white, usually formed roundly. Meatballs have health benefits for the human body because of the content contained in animal protein, vitamins and fat. However, in the manufacture of meatballs for the benefit of many, sellers often use the wrong way by using borax chemicals on meatballs. Therefore, this study aims to build a design tool in the form of borax detection on meatballs based on android. The tool works by processing the input data obtained from a color sensor coupled with an LED (Light Emitting Diode) to the microcontroller on Arduino Uno R3. The data is processed by implementing the Mamdani fuzzy logic method as a decision to state the output output of borax detector on meatballs. Furthermore, the output output displayed on the device using a sample of 12 meatballs obtained tool accuracy of 75%. Keywords : Boraks, Color Sensor, Fuzzy Logic, Microcontroller, Meatball.